Gender Differences in the Association Between Cataract and Mental Health in Adults With Diabetes: A Cross-Sectional Analysis From the Spanish National Health Survey 2017 - Guillermo F. López Sánchez; Lee Smith; Louis Jacob; Louis Jacob; Jae Il Shin; Ai Koyanagi; Ai Koyanagi; Shahina Pardhan (Frontiers Media S.A., 2021)
Objective: This study aimed to explore gender differences in the associations between cataracts and self-reported depression and chronic anxiety in Spanish adults with diabetes.Methods: Cross-sectional data from the Spanish Health Survey 2017 were analyzed. Inclusion criterion was a positive response to the question "Have you ever been diagnosed with diabetes?" Diabetes, cataracts, depression and chronic anxiety were based on self-reported lifetime diagnosis. Multivariable logistic regression was conducted to assess the association between cataracts and depression or anxiety among respondents with diabetes, stratifying by gender.Results: Out of a total 23,089 respondents, 2,266 people self-reported suffering from diabetes (50.2% women; average age 69.7 ± 12.7 years; age range 15-98 years). In people with diabetes, the presence of cataracts was associated with significantly higher odds for depression (OR = 1.655; 95% CI = 1.295-2.115). Gender-stratified analyses showed that only women with cataracts were significantly associated with higher odds for depression (OR = 1.762; 95% CI = 1.307-2.374) and chronic anxiety (OR = 1.519; 95% CI = 1.067-2.163).Conclusion: Cataracts are a significant risk factor for depression and chronic anxiety in Spanish women with diabetes, but not in men. Women with both diabetes and cataracts require assessment for depression and chronic anxiety, and possibly earlier interventions in order to reduce the potential risk of further mental health complications.